Prevalence and Characterization of Carbapenem-Hydrolyzing Class D β-Lactamase-Producing Acinetobacter Isolates From Ghana - Ayibieke, Alafate; Kobayashi, Ayumi; Suzuki, Masato; Sato, Wakana; Mahazu, Samiratu; Prah, Isaac; Mizoguchi, Miyuki; Moriya, Kyoji; Hayashi, Takaya; Suzuki, Toshihiko; Iwanaga, Shiroh; Ablordey, Anthony; et al. (Frontiers in Microbiology, 2020)
Multidrug resistance, especially carbapenem resistance in Acinetobacter bacteria is a global healthcare concern. However, available data on the phenotypic and genotypic characteristics of Acinetobacter isolates from West Africa, including Ghana is scanty. Our aim was to investigate the antibiotic resistance profile and genotypic characteristics of Acinetobacter isolates from Ghana and to characterize carbapenemase producers using whole-genome sequencing (WGS). A total of 36 Acinetobacter isolates collected at three hospitals in Ghana between 2016 and 2017 were analysed. MICs were determined by commercial antibiotic plates.Acinetobacter baumannii MLST was determined using the Pasteur scheme. WGS of OXAcarbapenemase producers was performed using short-and long-read sequencing strategies. The resistance rate was highest for trimethoprim/sulfamethoxazole (n = 22; 61%). Six (16.7%) and eight (22.2%) isolates were resistant to ceftazidime and colistin, respectively. Two (5.6%) isolates were resistant and one (2.8%) isolate had intermediate sensitivity to three carbapenems.Fifteen STs were identified in 24 A. baumannii isolates including six new STs (ST1467 ST1472). ST78 was the predominant (n = 6) followed by ST1469 (n = 3). Four carbapenemaseproducing A. baumannii isolates also were identified. Isogenic ST103 isolates Ab-B004d-c and Ab-D10a-a harboured blaOXA-23 within Tn2007 on identical plasmids, pAb-B004d-c_3, and pAb-D10a-a_3. ST1472 isolate Ab-C102 and ST107 isolate Ab-C63 carried blaOXA-58 and blaOXA-420, a rare blaOXA-58 variant, respectively, within novel genetic contexts. Our results show that A. baumannii isolates of diverse and unique genotypes, including OXA-carbapenemase producers, are circulating in Ghana highlighting the need for a wider surveillance of antimicrobial resistance.